MAKNA KEBAHAGIAAN DAN KEHARMONISAN RUMAH TANGGA DALAM PERSPEKTIF PSIKOLOGI - Mohamat Hadori; Minhaji Minhaji (LISAN AL-HAL: Jurnal Pengembangan Pemikiran dan Kebudayaan, 2018)
Happiness and harmony of household come from the love, emotional maturity, and intensity of communication that is built up from each individual in the household. The characteristic of a sense of love of the household is harmonious relationship especially between the husband and wife. In ddition to being a form of character and the personality of parents is also a means of forming the character and personality of child. Harmony of the home sourced from the harmony of each individual in the household that has performed its duties, functions, and responsibilities is a manifestation of an emotional maturity of each individual in the household. On the other hand, harmony of the household is a factor of communication intensity in family that runs effectively. The intensity of communication of the household has a considerable influence on whether or are not harmony Conversely relationships of family, ineffective communication is often the cause of harmony in a family relationship.